The MOSDEF survey: an improved Voronoi binning technique on spatially resolved stellar populations at z ∼ 2. Issue 4 (11th September 2020) - Fetherolf, Tara; Reddy, Naveen A; Shapley, Alice E; Kriek, Mariska; Siana, Brian; Coil, Alison L; Mobasher, Bahram; Freeman, William R; Sanders, Ryan L; Price, Sedona H; Shivaei, Irene; Azadi, Mojegan; et al.
ABSTRACT: We use a sample of 350 star-forming galaxies at 1.25 < z < 2.66 from the Multi-Object Spectrograph For Infra-Red Exploration (MOSFIRE) Deep Evolution Field survey to demonstrate an improved Voronoi binning technique that we use to study the properties of resolved stellar populations in z ∼ 2 galaxies. Stellar population and dust maps are constructed from the high-resolution CANDELS/3D- HST multiband imaging. Rather than constructing the layout of resolved elements (i.e. Voronoi bins) from the signal-to-noise (S/N) distribution of the H 160 -band alone, we introduce a modified Voronoi binning method that additionally incorporates the S/N distribution of several resolved filters. The spectral energy distribution (SED)-derived resolved E ( B − V )stars, stellar population ages, star-formation rates (SFRs), and stellar masses that are inferred from the Voronoi bins constructed from multiple filters are generally consistent with the properties inferred from the integrated photometry within the uncertainties, with the exception of the inferred E ( B − V )stars from our z ∼ 1.5 sample due to their UV slopes being unconstrained by the resolved photometry. The results from our multifilter Voronoi binning technique are compared to those derived from a 'traditional' single-filter Voronoi binning approach. We find that single-filter binning produces inferred E ( B − V )stars that are systematically redder by 0.02 mag, on average, but could differ by up to 0.20 mag and could be attributed to poorly constrained resolved photometry covering the UV slope. Overall, we advocate that our methodology produces more reliable SED-derived parameters due to the best-fitting resolved SEDs being better constrained at all resolved wavelengths – particularly those covering the UV slope.